Fungi of agricultural importance on fruit flies from Ica valley, Peru - Tipismana, Carlos E. (2005)
The present work reports the fungi isolated from specimens of the fruit flies of the genus Ceratitis (Macleay)and Anastrepha (Schiner) come from Ica valley, Peru. Fungi isolated were the genus Alternaria, Aspergillus, Cladosporium, Mucor, Penicillium, Rhizoctonia, Rhizopus, Trichoderma, as well as yeasts and sterile micelios. Counting was made in plate and it shows ranks between 8x103 to 8x104 UFC/g for Ceratitis; and 7x103 to 7x104 UFC/g for Anastrepha. The IVI% (Importance Value Index) indicated that Cladosporium has the greater ecological (78,05%). The Similarity Index between both genuses of analyzed fruit fly was 0,5. Results confirm fungi presence in fruit flies, and its possible impact to agricultural as vector agents of fungal diseases to local cultures.